Pengaruh Earnings Management, Political Connection dan Foreign Ownership terhadap Kinerja Perusahaan - Sitarisyah; Edi Sukarmanto (Bandung Conference Series: Accountancy, 2023)
Abstract. The large amount of stock investment that occurs in the mining sector will certainly affect the performance of mining companies. The company's performance can be seen from the financial condition of a company which is analyzed with financial analysis tools. Factors influencing this performance are Earnings Management, Political Connection and Foreign Ownership. This study aims to determine the magnitude of the influence of Earnings Management, Political Connection and Foreign Ownership on Company Performance (proxied by Tobins' Q) of Mining companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The method used in this study uses a quantitative approach. Applying the purposive sampling method so as to obtain a sample of 35 Mining companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The total data on the observation was 105 companies, and the data source used was secondary data obtained from the official website of the Indonesia Stock Exchange (IDX) and the website of each mining company with an observation period of 2019-2021. Hypothesis testing in this study used multiple regression analysis. The results of this study show that Earnings Management, Political Connection and Foreign Ownership affect the Company's Performance.Abstrak. Banyaknya investasi saham yang terjadi pada sektor pertambangan tentu akan mempengaruhi dalam kinerja perusahaan pertambangan. Kinerja perusahaan dapat dilihat dari kondisi keuangan suatu perusahaan yang dianalisis dengan alat-alat analisis keuangan. Faktor yang mempengaruhi kinerja ini adalah Earnings Management, Political Connection dan Foreign Ownership. Penelitian ini bertujuan untuk mengetahui besarnya pengaruh Earnings Management, Political Connection dan Foreign Ownership terhadap Kinerja Perusahaan (diproksikan dengan Tobins’ Q) perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2019-2021. Metode yang digunakan dalam penelitian ini menggunakan pendekatan kuantitatif. Menerapkan metode purposive sampling sehingga memperoleh sampel sebanyak 35 perusahaan Pertambangan Pertambangan yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2019-2021. Total data pada observasi sebanyak 105 perusahaan, dan sumber data yang digunakan adalah data sekunder yang diperoleh dari situs resmi Bursa Efek Indonesia (BEI) dan website masing-masing perusahaan pertambangan dengan periode pengamatan 2019-2021. Pengujian hipotesis dalam penelitian ini menggunakan analisis regresi berganda. Hasil penelitian ini menunjukkan bahwa Earnings Management, Political Connection dan Foreign Ownership berpengaruh terhadap Kinerja Perusahaan.